2001
DOI: 10.1287/ijoc.13.4.332.9732
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Programming Based Pruning Method for Decision Trees

Abstract: This paper concerns a decision-tree pruning method, a key issue in the development of decision trees. We propose a new method that applies the classical optimization technique, dynamic programming, to a decision-tree pruning procedure. We show that the proposed method generates a sequence of pruned trees that are optimal with respect to tree size. The dynamic-programming-based pruning (DPP) algorithm is then compared with cost-complexity pruning (CCP) in an experimental study. The results of our study indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Hence, the CCP method does not determine optimal solutions for each designated number of leaf nodes. Moreover, in the computational results presented in Li et al (2001), the DPP algorithm is shown to perform better than the CCP procedure in terms of classification accuracy. It is also worth noting that the sequence of pruned trees produced by the DPP approach are not necessarily nested, nor are they unique, but as Li et al (2001) argue, this issue is not of concern in regard to the quality of these trees.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Hence, the CCP method does not determine optimal solutions for each designated number of leaf nodes. Moreover, in the computational results presented in Li et al (2001), the DPP algorithm is shown to perform better than the CCP procedure in terms of classification accuracy. It is also worth noting that the sequence of pruned trees produced by the DPP approach are not necessarily nested, nor are they unique, but as Li et al (2001) argue, this issue is not of concern in regard to the quality of these trees.…”
Section: Introductionmentioning
confidence: 95%
“…Likewise, when minimizing the error measure defined by (5), we would like to force the tree to be pruned to a specified maximum size imposed by a side-constraint of the type h∈ z h ≤ E max . Observe that the DPP procedure discussed in §1 determines optimal solutions to the particular Problem PP1 with the additional constraint h∈ z h = E max simultaneously for all possible values of E max , and the CCP method solves this problem only for some subset of such values (see Li et al 2001 and the illustrative example given in §4). On the other hand, our modeling approach directly determines an optimal solution for any of the foregoing constraints having specified particular parameter values.…”
Section: Additional Side-constraintsmentioning
confidence: 99%
See 3 more Smart Citations